Comparative Effectivenesses of Pulsed Radiofrequency and Transforaminal Steroid Injection for Radicular Pain due to Disc Herniation: a Prospective Randomized Trial - Lee, Dong Gyu; Ahn, Sang-Ho; Lee, Jungwon (Journal of Korean medical science, 2016)
Transforaminal Epidural steroid injections (TFESI) have been widely adopted to alleviate and control radicular pain in accord with current guidelines. However, sometimes repeated steroid injections have adverse effects, and thus, this prospective randomized trial was undertaken to compare the effectivenesses of pulsed radiofrequency (PRF) administered to a targeted dorsal root ganglion (DRG) and TFESI for the treatment of radicular pain due to disc herniation. Subjects were recruited when first proved unsuccessful (defined as a score of > 4 on a visual analogue scale (VAS; 0-10 mm) and of > 30% according to the Oswestry Disability Index (ODI) or the Neck Disability Index (NDI)). Forty-four patients that met the inclusion criteria were enrolled. The 38 subjects were randomly assigned to receive either PRF (PRF group; n = 19) or additional TFESI (TFESI group; n = 19) and were then followed for 2, 4, 8, and 12 weeks. To evaluate pain intensity were assessed by VAS. ODI and NDI were applied to evaluate functional disability. Mean VAS scores for cervical and lumbar radicular pain were significantly lower 12 weeks after treatment in both study groups. NDI and ODI scores also declined after treatment. However, no statistically significant difference was observed between the PRF and TFESI groups in terms of VAS, ODI, or NDI scores at any time during follow-up. PRF administered to a DRG might be as effective as TFESI in terms of attenuating radicular pain caused by disc herniation, and its use would avoid the adverse effects of steroid.